Avoiding Fitnah: A Review of Islamic Communication Ethics - Muhammad Najmuddin; Kamaluddin Tajibu (Palakka : Media and Islamic Communication, 2023)
This research aims to examine the ethics of communication in the context of Islam, with a focus on avoiding slander. This study is conducted to understand the Islamic perspective on slander and provide guidelines for ethical communication that can be applied in daily life. The findings of the research show that Islam emphasizes the importance of communicating with good ethics, avoiding slander, and disseminating truthful and beneficial information. Slander is considered a serious sin in Islam because it can tarnish one's reputation, damage social relationships, and trigger conflicts in society. Therefore, Islamic ethics of communication stress the importance of verifying information before spreading it, combating gossip, and speaking with kind and meaningful words. This research contributes to understanding the ethics of communication in the context of Islam and the importance of avoiding slander. The implications of this research highlight the need for the application of Islamic principles of communication ethics in daily life, both in verbal and nonverbal communication, as well as in social media and the digital world. It is hoped that the findings of this research can provide practical guidance for Muslims in communicating with good ethics, building harmonious relationships, and strengthening unity in society.